Austerity, Youth Policy and the Deconstruction of the Youth Service in England - Davies, Bernard (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This timely book presents a vital analysis of the politics, policy and practice of youth work services in England and the impacts of the austerity agenda introduced after the 2007-08 financial crisis. Davies frames his research within the ideological, political and economic context of the last decade, contemplating the prescriptions of neoliberalism, and various other socio-political developments. He illustrates how wider government policies, programmes and initiatives have marred the purposes and methods of the Youth Service and youth work facilities, forging connections with what this means for young people and youth work. Unique in its depth and detail, this book is one of the first comprehensive, evidenced and up-to-date accounts of UK Youth Policy. It is an essential and invaluable resource for youth educators, researchers, service managers, practitioners and activists, as well as scholars and students of youth studies, social policy, public policy, and history.